Medical Malpractice of Vestibular Schwannoma: A 40-Year Review of the United States Legal Databases - Birkenbeuel, Jack (Otol Neurotol, 2019)
OBJECTIVES: To analyze medical malpractice lawsuit trends pertaining to cases of vestibular schwannomas (VS). METHODS: Two major computerized legal databases (Lexis-Nexis and WestLaw) were queried and reviewed for evaluation of all the US state and federal court records from civil trials alleging malpractice between 1976 and 2016. RESULTS: A total of 32 VS cases were identified. Allegations were divided into four categories: misdiagnosis/delayed diagnosis (47%), postoperative complications (44%), failure of informed consent or information sharing (16%), and other (3%). Postoperative complications included facial nerve paralysis, myocardial infarction, meningitis, and intracranial hemorrhage. Judgment amounts ranged from $300,000 to $2,000,000. The specialist type was specified for 24 of the 32 cases (75%): neurosurgeons (n = 9; 37%), neurotologists = (n = 6; 25%), general otolaryngologists (n = 5; 21%), primary care physicians (n = 4; 17%), neurologists (n = 3; 12%), radiologists (n = 3; 12%), anesthesiologists (n = 2; 8%), radiation oncologists (n = 1; 4%), and general surgeon (n = 1; 4%). Of these 24 cases, (n = 9; 37%) two or more physicians were named as defendants in the lawsuit. CONCLUSIONS: Enhanced physician-patient communication, ensuring proper and adequate patient consent procedures, and proper documentation are good practices that may decrease the likelihood of lawsuits.